Single port thoracic sympathectomy in Sharp syndrome - Misiak, Piotr; Wawrzynki, Marcin; Wcisło, Szymon; Jabłoński, Sławomir; Piskorz, Łukasz; Brocki, Marian; Kordiak, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
This article deals with an extremely rare case of the illness which was discovered for the very first time and named after Sharp in 1972. Due to it autoimmune background this condition was added to the scope of so called mixed connective tissue diseases. The rate of appearance is one case per one million of population. The illness often manifests itself initially in patients as young as 10 to 20 years old with symptoms like Raynaund’s syndrome in 75% to 100% of cases along with swelling of either whole hands or confined only the fingers (sausage-like fingers) which is peculiar to that condition. A 38 y.o. female patient showed up in our clinic complaining of paroxysmal excruciating pain in her fingers and we diagnosed her symptoms to be ischemic in their origin (constriction of the tiny arterioli is behind Raynuand’s syndrome). We also found others hallmarks of the condition such as skin callousness of her hands and hardly visible contractures in the fingers with range of motion impairment which clinched our diagnosis. The patient originally was scheduled for video-assisted thoracoscopic sympathectomy but when we got to know that her radiological exams reaveled no signs of any significant pathological changes within her chest we decided to carry out less invasive, newly introduced procedure – single port thoracic symphatectomy with videopleuroendoscope.